Prawa człowieka w Karcie Praw Podstawowych i ich miejsce w projekcie konstytucyjnym zjednoczonej Europy (Świat Idei i Polityki, 2005)
The aim of the analysis is to present a development of the human rights idea in the common legal system that is being created. The analysis concerns the Charter of Fundamental Rights proclaimed in 2000, being a document providing compliance with basic rights in the European Union order. Particular chapters emphasize that the Charter does not create new regulations but only gathers the existing ones, those already respected or at least observable, and puts them in one document. The paper also shows a significant role of general commissioners who are able and have courage, validating their opinions, to apply rightful solutions, though not in force officially. Another problem concerns issues which, in the Charter of Fundamental Rights, seem to be innovative or may become controversial in the future. As a summary, it was pointed that the birth of the Charter was justifiable, even if it is only journals of laws formulated in other legal acts.